Deterministic and probabilistic approaches to the denomination of the hydrochemical type of potentially medicinal groundwater from the “Zdrój Główny” intake (Krzeszowice, Poland) - Rusiniak, Piotr; Wątor, Katarzyna; Plata, Janusz (Geology, Geophysics and Environment, 2018)
The analysis and quality control of potentially curative water in Krzeszowice (Lesser Poland Region, Poland) has been carried out since 2002. The analyses are performed in the certified Hydrogeochemical Laboratory of the AGH University of Science and Technology and the laboratory of Provincial Environmental Protection Inspectorate in Krakow. The main purpose of this paper was to confirm the denomination of the hydrochemical type of water taken from “Zdroj Głowny” both for major ions and sulphur(II) compounds concentration which are specific components and assign curative properties to the examined water. On the basis of statistical analysis, it was stated that the concentrations of SO4, Ca, Mg, HCO3 and sulphur(II) compounds can be regarded as stable. Different methods of hydrochemical type determination lead to various classifications of groundwater. In the deterministic method and the probabilistic method with use of expanded uncertainty, the hydrochemical type of the examined water is SO4-Ca-Mg, S. In the probabilistic method where the standard deviation was taken into account, fewer components were in the hydrochemical type (SO4-Ca)-sulphur(II) compounds did not exceed the threshold value of 1 mg/L and, in this situation, the water cannot be regarded as potentially curative.